Chemical reprogramming regulates Tip60 expression to improve cleavage rates in somatic cell nuclear transfer reconstituted embryos of cashmere goats - Zhe, Xiaoshu; Zhang, Lihui; Ding, Rui; Ma, Hairui; Zhang, Yaoguang; Hao, Fei; Liu, Dongjun; Li, Yang (Frontiers in Veterinary Science, 2025)
The low efficiency of somatic cell nuclear transfer (SCNT) severely limits its application in animal cloning and regenerative medicine. To address this core scientific challenge, this study aims to explore a chemical reprogramming strategy that enhances the division rate of SCNT embryos during early developmental stages prior to transfer by pre-treating donor cells. Leveraging the role of small molecules in regulating cellular reprogramming, we designed a combination of small-molecule compounds (including 8 μM TranylcyprominT, 5 μM EPZ00477, 400 μM VPA, 8 μM Repsox, 1.2 μM PD0325901, 0.4 μM CHIR99021, 0.2 μM DZNeP, 8 μM Y-27632, and 1.2 μM UNC) to pre-treat donor cells, followed by embryo reconstruction and in vitro culture. Results demonstrated that this chemical treatment significantly improved embryo cleavage rates (35.59% vs. 46.15%). The combination of small molecules significantly upregulates the expression of core pluripotency genes (NANOG, SOX2, OCT4) and histone acetyltransferase TIP60 in donor cells. In summary, this study not only demonstrates the efficacy of chemical reprogramming in enhancing the early developmental capacity of SCNT embryos in large mammals but also lays a solid foundation for further elucidating its molecular mechanisms.